Challenges of information technology teacher education - Petkus, Tomas; Kurasova, Olga (Lietuvos matematikos rinkinys, 2014)
In the paper, challenges and problems of information technology teacher education have been investigated. Some reasons affecting a small number of applicants for programs, which leads to the right to work as information technology teachers have been analysed.
Keywords: information technologies; teacher education